2011
DOI: 10.1038/leu.2011.353
|View full text |Cite|
|
Sign up to set email alerts
|

RIP1 is required for IAP inhibitor-mediated sensitization of childhood acute leukemia cells to chemotherapy-induced apoptosis

Abstract: Evasion of apoptosis may contribute to poor treatment response in pediatric acute lymphoblastic leukemia (ALL), calling for novel treatment strategies. Here, we report that inhibitors of apoptosis (IAPs) at subtoxic concentrations cooperate with various anticancer drugs (that is, AraC, Gemcitabine, Cyclophosphamide, Doxorubicin, Etoposide, Vincristine and Taxol) to induce apoptosis in ALL cells in a synergistic manner as calculated by combination index and to reduce long-term clonogenic survival. Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 30 publications
4
55
2
Order By: Relevance
“…Previously, we reported that small-molecule inhibitors of IAP proteins such as Smac mimetics act in concert with other cytotoxic stimuli, for example death receptor ligands such as TRAIL and CD95 ligand, chemotherapeutic drugs, or irradiation, in ALL or other cancer entities. 24,25,38,[40][41][42][43] Second, we identify a novel underlying molecular mechanism of this synergistic interaction by showing that BV6 and dexamethasone act in concert to trigger proteasomal degradation of IAP proteins, which in turn promotes the assembly of the ripoptosome, a cytosolic cell death complex ( Figure 6). Several lines of evidence support this conclusion, as follows:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we reported that small-molecule inhibitors of IAP proteins such as Smac mimetics act in concert with other cytotoxic stimuli, for example death receptor ligands such as TRAIL and CD95 ligand, chemotherapeutic drugs, or irradiation, in ALL or other cancer entities. 24,25,38,[40][41][42][43] Second, we identify a novel underlying molecular mechanism of this synergistic interaction by showing that BV6 and dexamethasone act in concert to trigger proteasomal degradation of IAP proteins, which in turn promotes the assembly of the ripoptosome, a cytosolic cell death complex ( Figure 6). Several lines of evidence support this conclusion, as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia cells, human mesenchymal cells (MSCs), human G-CSF mobilized CD34 1 (immature) hematopoietic cells, monocytes, and dendritic cells were cultured as described previously 23,25 or as described in supplemental Methods BLOOD, 10 JULY 2014 x VOLUME 124, NUMBER 2 SYNERGISTIC LETHALITY OF Smac AND GLUCOCORTICOIDS 241…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Activation of RIPK1/RIPK3-dependent apoptosis or necroptosis typically requires additional modifiers, such as inhibition of cIAPs for activation of RIPK1 kinase-dependent apoptosis (73,74) and/or inhibition of caspase-8 for RIPK1/RIPK3 kinasedependent necroptosis (64,66,75,76). Consequently, Moriwaki et al examined cell death in response to a panel of commonly used chemotherapeutic agents and did not observe any changes in cell death upon knockdown of either RIPK1 or RIPK3 in RIPK3-expressing cells or upon overexpression of RIPK3 in cells that lost RIPK3 expression(37), suggesting that RIPK1/RIPK3 may not be generally involved in chemotherapy-induced cell death.…”
Section: Roles Of Ripk1/ripk3 In Immunogenic Cell Death Responses To mentioning
confidence: 99%